The mediating processes within social learning: women's food and water security practices in the rural Eastern Cape - Rivers, Nina (Rhodes University, Faculty of Education, Department of Education, 2016)
The focus of this study was to explore the implicit and explicit mediating processes within the social learning of women's food and water security practices in the rural Eastern Cape, South Africa. The study was undertaken in response to a growing problem of learning resources being decontextualised and therefore being of little relevance or use to the everyday practices of the people they were developed for. The central thesis of this study is that if the mediating processes that shape practice and learning are understood then these practices and learning can be better supported. One of the main foci of this study therefore is the concept of mediation and the importance of understanding the implicit and explicit mediating processes that shape learning and practice within the context of rainwater harvesting and food gardening practices of rural women. The study interprets these as social learning processes after the work of Lev Vygotsky and post-Vygotskian learning and activity development research, which recognises that all learning is socially mediated. This study also attempts to show that ontological factors also shape social learning processes via structural mediations (which are often also socially structured over time in history). Working within the broad framework of change oriented social learning, education for sustainability and the southern African water and food nexus the study is focused around two central research questions: 1) What are the mediating processes evident in and surrounding the learning of rainwater harvesting in the context of women's water and food security in rural communities? And 2) How can a question-based learning resource extend the learning practices in this context? Drawing on three sensitising concepts of dialectics, reflexivity and agency, the study worked with Cultural Historical Activity Theory (CHAT), underpinned by critical realism, to reveal how the learning of rainwater and food gardening practitioners is constrained and enabled by mediating processes. The theory of mediation provided a useful theoretical lens with which to examine data generated. A case study approach was used in two sites in the rural Eastern Cape. The first was Cata village in the Amathole district and the second was a peri-urban settlement called Glenconnor in the Cacadu district. Each case study is constituted within a networked activity system. The study also used a narrative inquiry approach in order to bring to life the case studies, activity systems and some of the dynamics of social learning within the study. The methodological tools of document analysis, observations, in-depth interviews and focus group discussions were used to explore the implicit and explicit mediating processes that shape research participants' rainwater harvesting and food gardening practices and their learning. Inductive, abductive and retroductive modes of inference were used to analyse data in and across case studies. One of the first findings of this study is that learning is embedded in and emergent from context in that it is mediated by implicit and explicit processes within each context. This makes such learning social, in the sense of social used by Vygotsky. The second finding showed that implicit and explicit mediation processes are constantly interacting in a dialectical process whether people are conscious of this interplay or not. This is an important dynamic to understand when trying to bring about societal transformation through education. Understanding the interaction between the implicit and explicit alerts researchers to the sociocultural dynamics inherent within social learning processes and therefore informs how learning resources and educational and development programmes should be designed and implemented. This study contributes to new knowledge in the environmental education field and the water knowledge sector. It makes a theoretical and empirical contribution to the body of knowledge concerned with socially mediated learning and situated learning approaches. The study illustrates how learning is embedded in context and also how learning emerges in relation to context via interactions between implicit and explicit mediation processes, and considers what this means for learning and development in the rural nexus of water and food security practices. This study also contributes to the growing body of post-Vygotskian social learning research in southern Africa that is being developed in the context of cultural historical activity theory as it shows the dialectical relationship that exists between implicit and explicit forms of mediation as these are embedded in, emergent from, and are externally mediated into activity systems in rural community contexts. This study contributes to a second area of knowledge: the water sector. With a background in anthropology which sensitised the researcher to contextual factors and approaching the study through an educational lens, the data has been worked with to surface and present the nuanced mediating processes that shape the learning and knowledge around water issues. This way of working and this focus on the socio-cultural is relatively new in the water sector in South Africa and gains significance in the light of an emergent interest in more complex social studies in the water sector which has traditionally been dominated by natural sciences and engineering. The significance of this study for rural South African women's lives is that by understanding and taking account of their history, context, struggles and experiences, their learning and practices can be better supported through more relevant learning resources and programmes.
Keywords: Uncatalogued